Successional patterns of microbial communities across various stages of leaf litter decomposition in poplar plantations - Hu, Shuang; Wang, Bao-Teng; Li, Taihua; Bu, Su; Jin, Chun-Zhi; Jin, Long; Ruan, Hong-Hua; Shin, Kee-Sun; Jin, Feng-Jie (Frontiers in Microbiology, 2025)
IntroductionLitter decomposition drives nutrient cycling in terrestrial ecosystems, yet the dynamics of phyllosphere microbial communities during this process remain poorly understood. Poplar leaf litter decomposition is particularly critical due to its widespread plantation use. While prior studies highlight the roles of microbes in decomposition, stage-specific community succession patterns and their driving factors are underexplored. We hypothesize that microbial structure and function correlate with litter nutrient dynamics. This work advances mechanistic insights into poplar litter decomposition and informs sustainable plantation management.MethodsPoplar leaf litter was sampled periodically during a 342-day decomposition period. DNA was extracted for 16S rRNA gene (bacteria) and ITS region (fungi) high-throughput sequencing. Microbial diversity, composition, and co-occurrence networks were analyzed using QIIME2 and Gephi. Litter quality was measured via elemental analysis and spectrophotometry. Canonical Correlation Analysis (CCA) was used to assess relationships between microbial communities and environmental factors.ResultsThe microbial community structure and composition exhibited significant differences at both the class and genus levels throughout the entire decomposition process. Specifically, the dominant fungal taxa, Dothideomycetes, was partially replaced by Sordariomycetes, Tremellomycetes and Leotiomycetes as degradation progressed. Meanwhile, Actinobacteria, Alphaproteobacteria, and Gammaproteobacteria dominated the bacterial communities throughout the entire degradation period, while the abundance of Gammaproteobacteria decreased at later stage and Actinobacteria peaked at t4 stage. Co-correlation networks revealed that the bacterial community had a higher average clustering coefficient and shorter average path lengths compared to fungi, suggesting greater functional diversity and resilience against external disturbances. With the decomposition of leaf litter, the total N content increased gradually, while other nutrients (C, P, K, cellulose and hemicellulose) decreased progressively. Litter characteristics had significant effects on microbial community structure: C/N, TK and residual hemicellulose (RH) were the primary driving factors affecting fungal community structure, whereas bacterial community structure was influenced by TK, RH, residual cellulose (RC) and lignin contents.ConclusionOverall, the decomposition of poplar litter is a complex process accompanied by dynamic succession of phyllosphere microbial communities. These results provide insights into the decomposition mechanisms of poplar leaf litter and offer a scientific basis for enhancing nutrient conversion efficiency and productivity of poplar plantations.